Patterns of Substance Use During Cognitive Enhancement Therapy: An 18-Month Randomized Feasibility Study. - Eack, Shaun M.; Hogarty, Susan S.; Bangalore, Srihari S.; Keshavan, Matcheri S.; Cornelius, Jack R. (Journal of Dual Diagnosis)
Objective: Substance use problems are common among people with schizophrenia, as are significant cognitive impairments. Because of potential shared neurobiological pathways, it is possible that cognitive remediation interventions may be associated with improvements in both substance use and cognition. This study examined the impact of cognitive remediation on alcohol and cannabis use and the cognitive correlates of changes in substance use among outpatients with schizophrenia. Methods: Individuals with schizophrenia who were receiving outpatient services at a psychiatric clinic and had moderate or higher addiction severity scores (N = 31) were randomized to 18 months of cognitive enhancement therapy (n = 22) or usual care (n = 9). Cognitive enhancement therapy is a cognitive remediation approach that integrates computer-based training in attention, memory, and problem solving with a group-based social cognition curriculum. Usual care was provided to all participants and consisted of routine psychiatric care. Primary outcomes included days of alcohol and cannabis use, assessed with the Timeline Followback method every six months and modeled using penalized quasi-likelihood growth curves. Results: Participants were on average 38.23 (SD = 13.44) years of age, had been ill for 14.19 (SD = 11.28) years, and were mostly male (n = 22, 71%), and about half were Caucasian (n = 16, 52%). Temporal patterns of substance use days were highly variable and followed nonlinear trajectories. Intent-to-treat analyses indicated that, compared to patients only receiving usual care, those receiving cognitive enhancement therapy were significantly less likely to use alcohol (OR =.22; 95% CI:.05,.90; p =.036), but not cannabis (OR = 1.89; 95% CI:.02, 142.99; p =.774) over time, and they reduced their alcohol use at significantly accelerated rates (OR = 1.02; 95% CI: 1.01, 1.03; p =.003). Changes in cognition were variably associated with substance use outcomes, although improvements in visual learning and reasoning and problem solving were both consistently related to reduced alcohol and cannabis use. Conclusions: Cognitive remediation may be effective for improving some substance use problems in schizophrenia. Visual learning and problem-solving deficits may be particularly important targets of such interventions, given their association with reduced alcohol and cannabis use. This study is registered at clinicaltrials.gov under #NCT01292577.